Implications of Article 28 H Verse (1) UUD 1945 Related To State Responsibilities In The Pandemic of Covid-19 - Yusuf Mardhani (Faculty of Law, Merdeka University Surabaya, 2020)
The 1945 Constitution has regulated the State's obligation to fulfill the right to life of its citizens, namely in Article 28 paragraph (1) of the 1945 Constitution.